1984
DOI: 10.1002/food.19840280645
|View full text |Cite
|
Sign up to set email alerts
|

Microecology of the gastrointestinal tract and the immunological status under food allergy

Abstract: In children suffering from food allergy the microecology of the gut and the immune status were examined. As a rule, sensitization due to the penetration of the epithelial barrier of the intestinum by macromolecules of the food is not accompanied by deficiency of secretory IgA. In all cases dysbacteriosis of different degree was observed with a characteristic picture of deficiency of Bifidobacteria and Lactobacilli combined with rising numbers of Enterobacteriaceae. Correlations to an altered immune response ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…and Bifidobacteria spp. have been shown to decrease, and levels of Enterobacteriaceae are increased [171] in individuals with food allergies. The addition of lactose to the diet modulates the composition of gut microbiota by increasing the total fecal counts of Lactobacillus spp.…”
Section: Intestinal Microbiota and Diseasementioning
confidence: 99%
“…and Bifidobacteria spp. have been shown to decrease, and levels of Enterobacteriaceae are increased [171] in individuals with food allergies. The addition of lactose to the diet modulates the composition of gut microbiota by increasing the total fecal counts of Lactobacillus spp.…”
Section: Intestinal Microbiota and Diseasementioning
confidence: 99%
“…All studies, except one, are presented and compared in Table 2 according to the type of atopic disease under study, the study population, design and methodology to examine the intestinal microbiota. One study (65) was not incorporated in Table 2, because it lacked statistical analysis and a reference group.…”
Section: Resultsmentioning
confidence: 99%
“…Already in the early 1980s, Russian scientists linked food allergy to abnormal intestinal microbiota (65). The authors examined 60 infants with dermatological syndrome, caused by food allergy and reported dysbacteriosis of different degrees in all cases.…”
Section: Culture-dependent Studiesmentioning
confidence: 99%
“…Culture-based approaches have suggested that the development of the GI microbiome is a progressive event beginning at birth and continuing until infants are weaned, with particular organisms acquired in distinct phases [6]. More recent, culture-independent studies have demonstrated that rather than a progressive colonization, the first year of life is characterized by fluctuating diversity of the microbial assemblage until convergence, with weaning, towards a GI community that more resembles that of an adult [7], [8], [9], [10]. As with adult GI bacterial consortia, inter-personal differences in GI microbial communities are evident in infants, particularly in the rate and stability of communities colonizing neonates [10], [11].…”
Section: Introductionmentioning
confidence: 99%
“…The first indication that a link existed between the GI microbiome and allergy was reported in the early 1980's in a study that described “dysbacteriosis” in infants with dermatological manifestations of food allergy, primarily due to low Bifidobacteria and Lactobacilli in combination with high numbers of species from the Enterobacteriaceae family [7]. Since then several studies have examined specific bacterial species in GI samples and demonstrated that their abundance correlated with atopy and asthma development [14], [15], [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%